2015
DOI: 10.1016/j.egypro.2015.11.764
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Teaching: Speech Production Accommodations Due to Changes in the Acoustic Environment

Abstract: School teachers have an elevated risk of voice problems due to the vocal demands in the workplace. This manuscript presents the results of three studies investigating teachers’ voice use at work. In the first study, 57 teachers were observed for 2 weeks (waking hours) to compare how they used their voice in the school environment and in non-school environments. In a second study, 45 participants performed a short vocal task in two different rooms: a variable acoustic room and an anechoic chamber. Subjects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
6
0
3
Order By: Relevance
“…Female teachers in factor 3 reported decreased ability to recover with rest in very large capacity classrooms compared to small, medium, and large capacity classrooms (7 out of a possible 12 for this factor). These results generally indicate a significant effect of the capacity (number of students) of classrooms on teachers reported amounts of vocal fatigue, which corresponds with previous work that room acoustics may affect teachers’ vocal health [23, 24].…”
Section: Discussionsupporting
confidence: 88%
“…Female teachers in factor 3 reported decreased ability to recover with rest in very large capacity classrooms compared to small, medium, and large capacity classrooms (7 out of a possible 12 for this factor). These results generally indicate a significant effect of the capacity (number of students) of classrooms on teachers reported amounts of vocal fatigue, which corresponds with previous work that room acoustics may affect teachers’ vocal health [23, 24].…”
Section: Discussionsupporting
confidence: 88%
“…For example, in a study of teachers’ voice use over several weeks of observation 19 , female teachers vocalized 10% more than males at work and 7% more outside of work. Further analysis of the same teachers showed that female teachers were more likely than their male counterparts to adjust their voice use due to situational need 30 . Higher vocal load would indicate more extensive vocal damage and, thus, more physical discomfort.…”
Section: Discussionmentioning
confidence: 98%
“…Various researchers have quoted various factors that can be associated with teacher's voice in a classroom. Some of these are working posture, teaching core subjects, classroom noise, voice ergonomic factors, presence or absence of sound amplification, teachers with voice problems, classroom capacity, gender, stress, speech style, room acoustics, vocal fatigue, acoustic environment, vocalisation time, reverberation and combined effect of noise and acoustics . These factors may act independently or may be linked to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Table 7 summarises the evidence of risk factors for voice problems in teachers. 21 presence or absence of sound amplification, 22 teachers with voice problems, 23 classroom capacity, 24 gender, 25 stress, 26 speech style, room acoustics, vocal fatigue, 27 acoustic environment, 28 vocalisation time, 29 reverberation 30 and combined effect of noise and acoustics. 31 These factors may act independently or may be linked to each other.…”
Section: Discussionmentioning
confidence: 99%